Intrauterine interventions for women with two or more implantation failures: A systematic review and network meta-analysis - Jin, Xin Hang; Li, Yang; Li, Dan (Frontiers in Endocrinology, 2022)
Objective: To compare the effectiveness of different intrauterine interventions for women with two or more unexplained implantation failures. Design: A systematic review and network meta-analysis of randomized controlled trials(RCTs). Patient(s): Women with two or more implantation failures undergoing fresh or frozen embryo transfer(ET). Intervention(s): An electronic search of the following databases: Pubmed, Cochrane Central Register of Controlled Trials(CENTRAL), and Embase. Main Outcome Measure(s): Clinical pregnancy, live birth/ongoing pregnancy, and miscarriage. Result(s): We included 21 RCTs(3079 women) in the network meta-analysis. The network meta-analysis showed that compared with control treatment, platelet-rich plasma(PRP), peripheral blood mononuclear cell(PBMC), granulocyte colony-stimulating factor(G-CSF), human chorionic gonadotropin(HCG), and endometrial scratch(ES) significantly increased clinical pregnancy(OR 3.78, 95% CI 2.72 to 5.25; 2.79, 95% CI 1.75 to 4.45; 1.93, 95% CI 1.37 to 2.72; 1.80, 95% CI 1.18 to 2.72; 1.75, 95% CI 1.29 to 2.36, respectively). PRP ranked the highest in improving clinical pregnancy, followed by PBMC, G-CSF, HCG, and ES. Compared with control treatment, PRP, PBMC, and ES significantly increased live birth/ongoing pregnancy((OR 5.96, 95% CI 3.38 to 10.52; OR 2.55, 95% CI 1.27 to 5.11; OR 1.70, 95% CI 1.07 to 2.69, respectively). PRP ranked the highest in improving live birth/ongoing pregnancy, followed by PBMC, and ES. Conclusion(s): PRP is the most effective intrauterine intervention in improving pregnancy outcome in women with two or more implantation failures.